1996
DOI: 10.1038/bjc.1996.477
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in NAD(P)H:quinone oxidoreductase (NQO1): relationship of a homozygous mutation at position 609 of the NQO1 cDNA to NQO1 activity

Abstract: A polymorphism in NAD(P)H:quinone oxidoreductase (NQO1): relationship of a homozygous mutation at position 609 of the NQO1 cDNA to NQO1 activity Sir -NQO1 has attracted considerable attention owing to its ability to deactivate a broad range of xenobiotics while activating certain anti-tumour quinones (Ross et al., 1994). A number of recent reports have highlighted the occurrence and potential significance of a point mutation in the NQO1 gene which is associated with a loss of NQO1 activity in both normal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 6 publications
2
39
0
2
Order By: Relevance
“…Recently, a polymorphism of the gene encoding NQO1 has been described. The polymorphic variant of the gene (a C to T transition at base pair 609, codon 187) is associated with reduced NQO1 activity (Ross et al, 1996;Siegel et al, 1999). The three genotypes of this gene are the homozygous wild-type C/ C (normal activity), the heterozygous C/T genotype (mild activity), and the homozygous rare allele T/T genotype (2-4% of normal activity).…”
Section: Carcinogen Metabolismmentioning
confidence: 99%
“…Recently, a polymorphism of the gene encoding NQO1 has been described. The polymorphic variant of the gene (a C to T transition at base pair 609, codon 187) is associated with reduced NQO1 activity (Ross et al, 1996;Siegel et al, 1999). The three genotypes of this gene are the homozygous wild-type C/ C (normal activity), the heterozygous C/T genotype (mild activity), and the homozygous rare allele T/T genotype (2-4% of normal activity).…”
Section: Carcinogen Metabolismmentioning
confidence: 99%
“…As a clear gene-dose effect was suggested by the genotype-phenotype association studies, [21][22][23][24][25] a genetic model (codominant or decreasing model), in which lung cancer risks of the genotypes Pro/Pro, Pro/Ser, and Ser/Ser decrease in that order, was applied. As the Ser/Ser genotype has not been separated due to a low prevalence of the rare Ser allele in several studies, we combined the Pro/Ser genotype with Ser/Ser genotype.…”
Section: Associations Nqo1 Pro187ser Polymorphism and Lung Cancer Riskmentioning
confidence: 99%
“…The three genotypes of this gene are the Pro/Pro (normal activity), the Pro/Ser (mild activity), and the Ser/Ser (2-4% of normal activity). [21][22][23][24][25] The genotype frequencies in different populations are shown in Table 1. 26 -65 The summary frequency of the Ser allele among Caucasians was 18.9% (95% CI ϭ 15.6 -22.1%), and the summary frequency of the Ser/Ser and Pro/Ser genotypes combined was 31.8% (95% CI ϭ 30.0 -33.7%).…”
mentioning
confidence: 99%
“…Phase II enzymes catalyse the conversion of quinones to hydroquinones, which are readily excreted by the body. However, the Pro-toSer substitution in NQO1 is associated with a loss of enzyme function because of protein instability [16,17]. In our study, patients with an NQO1-Ser/Ser genotype showed a better response to surgical repair.…”
Section: Discussionmentioning
confidence: 51%
“…NAD(P)H:quinone oxidoreductase 1 (NQO1) is a cytosolic enzyme that induces two-electron reduction of quinoid compounds to hydroquinones, a less toxic form, thus avoiding free radical formation. A sequence variant at position 609 (C-to-T, proline [Pro]-to serine [Ser], rs1800566 at dbSNP) in the NQO1 gene encodes for an enzyme with reduced quinone reductase activity, which has been hypothesized to affect cancer susceptibility [16,17].…”
Section: Introductionmentioning
confidence: 99%